A cross-sectional study of retinal vessel changes based on optical coherence tomography angiography in Alzheimer’s disease and mild cognitive impairment - Ma, Xiaoyu; Xie, Zengmai; Wang, Huan; Tian, Zhongping; Bi, Yanlong; Li, Yunxia; Zhang, Li (Frontiers in Aging Neuroscience, 2023)
Background The involvement of retina and its vasculature has been recently described in Alzheimer’s disease (AD). Optical coherence tomography angiography (OCTA) is noninvasively used to assess the retinal blood flow. Objective This study was to compare vessel density (VD) and blood perfusion density (PD) of the macular in AD patients, mild cognitive impairment (MCI) patients and healthy controls by OCTA, which may provide new ideas for diagnosis of AD or MCI. Methods AD patients, MCI patients and healthy controls underwent a comprehensive ophthalmic and neurological evaluations, including cognitive function assessments as well as visual acuity, intraocular pressure (IOP), slit lamp examinations, and OCTA. General demographic data, cognitive function, retinal VD and PD were compared among three groups. The correlations among retinal VD, PD and cognitive function, amyloid-beta (Aβ) protein and phosphorylated Tau (p-Tau) protein were further evaluated. The correlations between retinal superficial capillary plexus and cognitive function, Aβ protein and p-Tau protein were also explored. Results A total of 139 participants were recruited into this study, including 43 AD patients, 62 MCI patients, and 34 healthy controls. After adjusting for sex, age, history of smoking, history of alcohol intake, hypertension, hyperlipidemia, best corrected visual acuity, and IOP, VD and PD in the nasal and inferior regions of the inner ring, superior and inferior regions of outer ring in the AD group were significantly lower than in the control group (p < 0.05). PD in nasal region of outer ring also significantly decreased in the AD group. VD and PD in superior and inferior regions of inner ring, superior and temporal regions of outer ring in the MCI group were markedly lower than in the control group (p < 0.05). After adjusting for sex and age, VD and PD were correlated with Montreal Cognitive Assessment Basic score, Mini-mental State Examination score, visuospatial function and executive function (p < 0.05), while Aβ protein and p-Tau protein had no relationship with VD and PD. Conclusion Our findings suggest that superficial retinal VD and PD in macula may be potential non-invasive biomarkers for AD and MCI, and these vascular parameters correlate with cognitive function.